Get Help / Agalya Aishani Senthil Ilangovan … [ et al.] - Senthil Ilangovan, Agalya Aishani; Ganesan, Kavisha; Mani Vannan Natarajan, Keerthini; Dev Anand, Tharshen; Sivakumar, Rathinaganessha (Faculty of Computer and Mathematical Sciences, 2021)
Our project, Get Help not only provides help and services to those who need it but also provides job vacancies especially during this pandemic. Our website provides a wide range of services from plumbing to hospitality. Our website provides benefits to everyone including those who have lost their jobs to become part of our project simply by heading to our website and filling up a registration form based on their respective fields. Through this project, citizens will be able to put their skill into use. Get Help website has multiple tabs for specific purposes such as, information about us, provided servicer and job application forms. Our website can be accessed by anyone irrespective of gender, social status and race at anytime. Most importantly, the design of the website is made user friendly and it wouldn’t be a hassle to access.